Crisis? What crisis?: Why the economic and financial crisis is a blind spot for European foundations - Fioramonti, Lorenzo; Thümler, Ekkehard (Effect, 2013)
The financial crisis and the malfeasance of the financial industry are almost entirely absent from the discourse and practice of Europe’s foundations, which only appear to care about the crisis when it affects their own assets. Are these issues
Gesehen am 20.06.2023